Upaya Pencegahan Stunting Melalui Edukasi Pemberian Makanan Pendamping Asi Di Desa Jiwan - Fitriana Noor Khayati; Marwanti Marwanti; Dita Tri Wahyuningsih; Gesti Wulandari (WASATHON Jurnal Pengabdian Masyarakat, 2024)
Under five years is a golden period that must be considered capital for life in the next age. The problem of fulfilling nutrition in toddlers, especially those aged 6-24, needs attention. At 6-24 months, children need to receive complementary foods of breastfeeding/ Makanan Pendamping ASI (MP-ASI) that are nutritious and given in the right way. It is hoped that providing good MP-ASI can optimize children's growth and development, including preventing stunting. Many parents still don't understand when to start giving MP-ASI, including the type and method, they need to get education from health workers. Jiwan Village is one of the villages located approximately 13 km from the city center of Klaten and some mothers with toddlers have given MP-ASI before the age of 6 months. This activity aims to provide education on providing MP-ASI to mothers with children aged 6-24 months in Jiwan Village. Educational activities conducted using brainstorming methods and question-and-answer lectures. The media used are modules and audiovisual media. Activities were carried out in Jiwan Village. The results of the activity showed that the average pre-test knowledge was 74.62 and the average post-test knowledge was 77.52. This shows an increase in knowledge of complementary breastfeeding. Future suggestions include education using practical methods for complementary breast milk food menus. Aspects of knowledge that still need to be improved are the timing of giving MP-ASI, the equipment used in giving MP-ASI.